Peran Moderasi Religiusitas pada Pengaruh Lokasi dan Pembiayaan Syariah terhadap Keputusan Pembelian Rumah (Di Perumahan Griya Darussalam Resort) - Febri, Febrianti; Farild, Miftha (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This research aims to determine the moderating role of religiosity on the influence of location and sharia financing on house purchase decisions (at GriyaDarussalam Resort Housing). This research is quantitative research and the data source in this research is primary data where the data collection method uses questionnaires distributed to residents in the Griya Darussalam Resort housing complex. The sampling technique used in this research is purposive sampling using the Slovin formula. So as many as 100 respondents were obtained. By processing primary data using Structural Equation Modeling (SEM) using SmartPLS version 4.1 for Windows. The results of this study show that the Location variable has a positive and significant effect on house purchasing decisions, Sharia Financing has a positive and significant effect on house purchasing decisions, Religiosity cannot moderates the influence of location on the decision to buy a house and religiosity is able to moderate the influence of Sharia financing on the decision to buy a house.